Contract Workers in Japan's Nuclear Utility Industry: Can We Maintain Safety and Health Standards at Nuclear Power Plants? - Matsumoto, Akikuni; Hara, Hisayuki; Nawata, Kazumitsu (Journal of Reviews on Global Economics, 2014)
: Many small contracting firms are used to maintain nuclear power plants in Japan. The accident at the Fukushima nuclear plant raised the serious question as to whether safety standards can be upheld with this system. A review of regulations governing Japan's nuclear utility industry derived two imperfect information models that implied opposing incentives for utility companies to use contract workers rather than hire employees. We then analyzed the dataset of nuclear plant worker's exposure to radiation in the power generation industry. The results suggest that using contract workers enables the utility companies to implement lower standards than those imposed by regulations and to reduce costs by circumventing responsibilities legally imposed on employers.